Manejo de coberturas vegetais na cultura da soja. - Lima, Gislaine Piccolo de (2008)
The cover crop adequacy to the implanted crop together with the adopted soil management system is important in order to obtain improvements on the system s yield and efficiency. Thus, this study aimed at examining the possible allelopathyc interference of black oat remains (Avena strigosa Schreb) and a consortium of black oat, forage turnip (Raphanus sativus L.) and vetch (Vicia sativa L.) on the speed emergency index (SEI) and emergency speed (ES) of seedlings, plants heights, weed incidence (large and narrow leaf), harvested seed quality and soybean yield Glycine max (L.) Merrill; considering different intervals among drying of cover crop using the Glyphosate 480 (3L ha-1) herbicide and the sowing of BRS 232 soybeans. The plots were marked on the field measuring 5 m x 2.5 m, adding 1 m borderline between them to the four treatment distributions for black oat cover, four treatments, the consortium and a control for each cover crop, completely randomized, with five replications. The cover crop was sowed in August, 2006; each row was 0.15m distant from each viii other. Later, the plots were dried on intervals of ten, twenty and thirty days before the soybean sowing, which was installed in November, 2006, with the 13 rows; each row was 0.45 m distant from each other and there were 14 seeds per linear meter. All the tests were submitted to an experimental design, with subdivided plots (split plot), completely randomized; the averages were also compared using Scott and Knott test at 5 % of significance. The study observed possible allelopathyc interference of cover crop on SEI, harvested seed quality, weed as well as the intervals of sowing and drying.